Analysis of accuracy in optical motion capture - A protocol for laboratory setup evaluation - Eichelberger, P.; Ferraro, M.; Minder, U.; Denton, T.; Blasimann, A.; Krause, F.; Baur, H. (Journal of Biomechanics, 2016)
Validity and reliability as scientific quality criteria have to be considered when using optical motion capture (OMC) for research purposes. Literature and standards recommend individual laboratory setup evaluation. However, system characteristics such as trueness, precision and uncertainty are often not addressed in scientific reports on 3D human movement analysis. One reason may be the lack of simple and practical methods for evaluating accuracy parameters of OMC.